Exopolysaccharides from camel milk-derived Limosilactobacillus reuteri C66: Structural characterization, bioactive and rheological properties for food applications - Kober, A. K. M. Humayun; Abdin, Mohamed; Subhash, Athira; Liu, Shao-Quan; Dertli, Enes; Abu-Jdayil, Basim; Show, Pau-Loke; Ayyash, Mutamed (ELSEVIER, 2025)
Microbial exopolysaccharides (EPS) are valued as safe, functional bio-ingredients in food. Produced by microorganisms like lactic acid bacteria (LAB), they enhance the rheological and sensory properties of food products. In this study, Limosilactobacillus reuteri C66 (EPS-C66), was utilized to produce EPS. EPS-C66 was isolated, purified, and characterized for its rheological properties and biofunctionalities. Molecular weight was 3.7 x 105 Da. Three monosaccharides (arabinose, mannose, and glucose) were identified. At 10 mg/mL, EPS-C66 exhibited significant scavenging activity against DPPH and ABTS radicals, achieving 67.9 % and 31.3 %, respectively. Additionally, it reduced the viability of Caco-2 and MCF-7 cancer cells by 93.7 % and 61.4 %, respectively. EPSC66 also demonstrated antibacterial effects against S. aureus, S. typhimurium, L. monocytogenes, and E. coli, with ranges of 5.9, 6.1, 6.0, and 5.7 log CFU/mL, respectively. The current study highlights that EPS-C66 can enhance the health benefits and rheological properties of foods, contributing to the development of novel functional foods.
Keywords: Exopolysaccharides; Limosilactobacillus reuteri; Rheological properties; ACE-inhibition; Antioxidants; LACTIC-ACID BACTERIA; LACTOBACILLUS-REUTERI; Chemistry; Food Science & Technology